2020
DOI: 10.35848/1347-4065/ab8bbf
|View full text |Cite
|
Sign up to set email alerts
|

Review on ferroelectric/polar metals

Abstract: The possibility of reconciliation between seemingly mutually exclusive properties in one system can not only lead to theoretical breakthroughs but also potential novel applications. The research on the coexistence of two purportedly contra-indicated properties, ferroelectricity/polarity and conductivity, proposed by Anderson and Blount over 50 years ago was recently revitalized by the discovery of the first unambiguous polar metal LiOsO 3 and further fueled by the demonstration of the first switchable ferroele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 128 publications
(489 reference statements)
0
33
0
Order By: Relevance
“…Polarization switching has been employed in capacitive ferroelectric memories, where opposed. [23,24] In turn, it is highly nontrivial to establish good electrical contact to the domain wall. [25] In fact, charged domain walls may reconstruct in the contact region preventing good metallic contact from being established on an intrinsic level.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization switching has been employed in capacitive ferroelectric memories, where opposed. [23,24] In turn, it is highly nontrivial to establish good electrical contact to the domain wall. [25] In fact, charged domain walls may reconstruct in the contact region preventing good metallic contact from being established on an intrinsic level.…”
Section: Introductionmentioning
confidence: 99%
“…Strain-dependent ferroelectricity in stoichiometric G-AFM SMO thin films was previously reported by Marthinsen et al 12 Here, we evaluate polar instabilities also for the FM phase but note that its metallicity will preclude ferroelectric switching, an unstable polar mode indicating merely a polar metal state. 47,48 Fig. 2 shows the evolution of SMO polar-mode frequencies as a function of strain.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, another pair of contraindicated propertiesïŁżFE and metallicityïŁżhas strongly attracted attention from the research community, which is called polar metal (or ferroelectric metal). [ 18 ] Moreover, theoretical predictions and experimental observations have confirmed that the polarization reversal can be achieved in polar metals LiOsO 3 ultrathin film, [ 19 ] Bi 5 Ti 5 O 17 , [ 20 ] and 2D WTe 2 [ 21 ] by applying an electric field. In 2015, Puggioni et al [ 22 ] predicted that (LiOsO 3 ) 1 /(LiNbO 3 ) 1 superlattice polar metal exhibits strong ME coupling as well as high ferroelectric Curie temperature (927 K) and NĂ©el temperature (379 K).…”
Section: Introductionmentioning
confidence: 88%